Biomimetic Synthesis of Calcium Carbonate in the Sucrose Solution - YAO*, CHENG-LI; XU†, WANG-HUA; DING, AI-MIN; ZHU, JIN-MIAO (Asian Journal of Chemistry, 2009)
Many studies showed that saccharides or polysaccharides play animportant role in the process of biomineralization. In this work, sucrosewas used to induce the formation of calcium carbonate. The CaCO3crystals were characterized by scanning electron microscope (SEM),Fourier transform infrared spectrograph (FT-IR) and powder X-raydiffractometry (XRD). The results showed vaterite formed easily in thesucrose solution.